PENYEGARAN KADER TENTANG TANDA – TANDA KEHAMILAN, CARA MENGATASI MASALAH KEHAMILAN DAN PERSIAPAN PERSALINAN DI LINGKUNGAN WILAYAH KERJA PUSKESMAS SRONDOL KOTA SEMARANG - Kurniati Puji Lestari; Elisa Elisa; Iis Sriningsih; Budiyati Budiyati; Tri Wiji Lestari; Wagiyo Wagiyo; Desak Made Parwati; Titin Suheri; Lucia Endang Hartati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2016)
Strategies to decrease mortality is by improving the knowledge of pregnant women about monitoring of pregnant women includes signs of pregnancy, how to deal with complaints of pregnancy, adaptation to the changes of pregnancy, childbirth, postnatal care, baby care, myth, infectious diseases and birth certificate and the baby's health. Volunteer role to support P4K program (Program Planning Maternity Complications Prevention). Volunteer is largely a PKK member, is expected to act as a conduit of information to the public health, community mobilization to carry health messages. Volunteer can also serve as the first person to discover if there are health problems in the area and immediately report to local health workers. The implementation of community service performed in the Environment of Puskesmas Srondol Semarang from June 22 until July 31, 2015 (6 weeks), includes planning, coordination, implementation increased knowledge of health volunteers include refresher volunteer of sign of pregnancy, how to resolve the problem pregnancy and childbirth. The method used in this service activity is to provide materials through refresher volunteer and interactive discussion, preceded by a pre-test and post-test.